Soil nitrogen and carbon storages and carbon pool management index under sustainable conservation tillage strategy - Yuan, Jianyu; Liang, Yunliang; Zhuo, Macao; Sadiq, Mahran; Liu, Li; Wu, Jiangqi; Xu, Guorong; Liu, Shuainan; Li, Guang; Yan, Lijuan (Frontiers in Ecology and Evolution, 2023)
Agricultural practices are significant to increase the soil nitrogen and organic carbon sequestration to adapt and mitigate the climate change in a recent climate change scenario. With this background, we carried out research in the Longzhong Loess Plateau region of China. This research was conducted under a randomized complete block design, with three replicates. Adopt the method of combining outdoor positioning field test with indoor index measurement to explore the soil bulk density (BD), nitrogen components (viz., nitrate nitrogen (NO3--N), ammonia nitrogen (NH4+-N), total nitrogen (TN), microbial biomass nitrogen (MBN) and nitrogen storage (NS), and carbon components (viz., soil organic carbon (SOC), easily oxidized organic carbon (EOC), microbial biomass carbon (MBC) and carbon storage (CS), carbon pool index (CPI), carbon pool activity (A) and carbon pool activity index (AI) and carbon pool management index (CPMI)) and C/N, ratio under different tillage practices (namely., conventional tillage (CT), no tillage (NT), straw mulch with conventional tillage (CTS) and straw mulch with no tillage (NTS). Our results depicted that different conservation tillage systems significantly increased soil BD over conventional tillage. Compared with CT, the NTS, CTS and NT reduced soil NO3--N, increased the soil NH4+-N, TN, MBN and NS, among them, NS under NTS, CTS and NT treatment was 25.0%, 14.8% and 13.1% higher than that under CT treatment respectively. Additionally, conservation tillage significantly increased SOC, EOC, MBC, CS, CPI, AI, CPMI and C/N, ratio than CT. Inside, CS under NTS, CTS and NT treatment was 19.4%, 12.1% and 13.4% higher than that under CT treatment respectively. Moreover, during the 3-year study period, the CPMI under NTS treatment was the largest (139.26, 140.97 and 166.17). Consequently, we suggest that NTS treatment was more sustainable strategy over other investigated conservation tillage practices and should be recommended as climate mitigation technique under climate change context.